2017
DOI: 10.1038/nature22964
|View full text |Cite|
|
Sign up to set email alerts
|

mTORC1-dependent AMD1 regulation sustains polyamine metabolism in prostate cancer

Abstract: Activation of the PTEN-PI3K-mTORC1 pathway consolidates metabolic programs that sustain cancer cell growth and proliferation1,2. Here we show that mTORC1 regulates polyamine dynamics, a metabolic route that is essential for oncogenicity. Through the use of integrative metabolomics in a mouse model3 and human biopsies4 of prostate cancer, we identified alterations in tumours impacting on the production of decarboxylated S-adenosylmethionine (dcSAM) and polyamine synthesis. Mechanistically, this metabolic rewiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
168
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(182 citation statements)
references
References 47 publications
14
168
0
Order By: Relevance
“…SOD1 however has been only recently been proposed as a novel target for cancer therapy [24] and its role in cancer is also being revealed [25]. More recently being elucidated is the role of AMD1 in cancer which has been found to be upregulated in human prostate cancer [26]. NOS2 is another one which has been recently being seen as a emerging target for cancer treatment [27][28].…”
Section: Resultsmentioning
confidence: 99%
“…SOD1 however has been only recently been proposed as a novel target for cancer therapy [24] and its role in cancer is also being revealed [25]. More recently being elucidated is the role of AMD1 in cancer which has been found to be upregulated in human prostate cancer [26]. NOS2 is another one which has been recently being seen as a emerging target for cancer treatment [27][28].…”
Section: Resultsmentioning
confidence: 99%
“…However, the larger picture of mTORC1-mediated metabolic regulation and how it drives cellular oncogenesis is still an active and attractive area of research. In a recent issue of Nature , Zabala-Letona et al (2017) demonstrate that in addition to the previously reported roles in driving anabolic processes, mTORC1 regulates polyamine flux to promote cell proliferation and growth in prostate cancer.…”
mentioning
confidence: 86%
“…Reporting recently in Nature , Zabala-Letona et al (2017) show that mTORC1 regulates an additional branch of metabolism in the cell—polyamine synthesis—that is important for prostate cancer tumorigenicity. …”
mentioning
confidence: 99%
See 2 more Smart Citations